Effects of fructose-induced metabolic syndrome on rat skeletal cells and tissue, and their responses to metformin treatment - Felice, Juan Ignacio (2017)
Aims: Deleterious effects of metabolic syndrome (MS) on bone are still controversial. In this study we evaluated the effects of a fructose-induced MS, and/or an oral treatment with metformin on the osteogenic potential of bone marrow mesenchymal stromal cells (MSC), as well as on bone formation and architecture. Methods: 32 male 8 week-old Wistar rats were assigned to four groups: control (C), control plus oral metformin (CM), rats receiving 10% fructose in drinking water (FRD), and FRD plus metformin (FRDM). Samples were collected to measure blood parameters, and to perform pQCT analysis and static and dynamic histomorphometry. MSC were isolated to determine their osteogenic potential. Results: Metformin improved blood parameters in FRDM rats. pQCTand static and dynamic histomorphometry showed no significant differences in trabecular and cortical bone parameters among groups. FRD reduced TRAP expression and osteocyte density in trabecular bone and metformin only normalized osteocyte density. FRD decreased the osteogenic potential of MSC and metformin administration could revert some of these parameters. Conclusions: FRD-induced MS shows reduction in MSC osteogenic potential, in osteocyte density and in TRAP activity. Oral metformin treatment was able to prevent trabecular osteocyte loss and the reduction in extracellular mineralization induced by FRD-induced MS.